Bronchoalveolar lavage fluid findings in patients with chronic hepatitis C virus infection. Issue 3 (March 1996) - Kubo, K; Yamaguchi, S; Fujimoto, K; Hanaoka, M; Hayasaka, M; Honda, T; Sodeyama, T; Kiyosawa, K
Abstract : BACKGROUND: Hepatitis C virus (HCV) infection has recently been incriminated as an aetiological agent in idiopathic pulmonary fibrosis. This study was performed to determine the cellularity and lymphocyte phenotypes of bronchoalveolar lavage (BAL) fluid in patients with chronic hepatitis C. METHODS: BAL fluid and lavage lymphocyte subsets from 13 patients (10 men) with active chronic hepatitis C, diagnosed by sustained elevated serum glutamic pyruvic transaminase and typical histological findings in the liver, were analysed. Lavage findings in these patients were compared with those from 13 healthy volunteers (eight men) as controls. RESULTS: There was no difference in total cell counts in lavage fluid between the two groups. Lavage lymphocyte and eosinophil numbers were increased in patients with chronic hepatitis C. Surface marker analysis of the lymphocyte populations showed increases in CD2, CD3, CD4, and HLA-DR. CD4/CD8 ratios were not different. CONCLUSIONS: The numbers of lymphocytes and eosinophils in BAL fluid are increased in patients with chronic hepatitis C. These findings suggest that HCV infection may trigger alveolitis.